Effective combination of non-thermal plasma and catalyst for removal of volatile organic compounds and NOx - Jeon, Sang Goo; Kim, Kwang-Ho; Shin, Dae Hyun; Nho, Nam-Sun; Lee, Kyong-Hwan (The Korean journal of chemical engineering, 2007)
gies. A two-plasma/catalyst hybrid system was used to decompose VOCs (toluene) and NOx at temperature lower than150oC. The single-stage type (Plasma-driven catalyst process) is the system in which catalysts are installed in a non-thermal plasma reactor. And the two-stage type (Plasma-enhanced process) is the system in which a plasma and a cat-alyst reactor are connected in series. The catalysts prepared in this experiment were Pt/TiO2 and Pt/Al2O3 of powdertype and Pd/ZrO2, Pt/ZrO2 and Pt/Al2O3 which were catalysts of honeycomb type. When a plasma-driven catalyst reactorwith Pt/Al2O3 decomposed only toluene, it removed just more 20% than the only plasma reactor but the selectivity ofCO2 was remarkably elevated as compared with only the plasma reactor. In case of decomposing VOCs (toluene) andNOx using plasma-enhanced catalyst reactor with Pt/ZrO2 or Pt/Al2O3, the conversion of toluene to CO2 was nearly100% and about 80% of NOx was removed. KCI Citation Count: 6